Antimicrobial activity of natural products against Helicobacter pylori: a review - Bonifacio, Bruna Vidal [UNESP]; Santos Ramos, Matheus Aparecido dos [UNESP]; Silva, Patricia Bento da [UNESP]; Bauab, Taís Maria [UNESP] (Biomed Central Ltd, 2014)
Throughout the genetic and physiological evolution of microorganisms, the microbiological sciences have been expanding the introduction of new therapeutic trials against microbial diseases. Special attention has been paid to the bacterium Helicobacter pylori, which induces gastric infections capable of causing damage, ranging from acute and chronic gastritis to the development of gastric cancer and death. The use of compounds with natural origins has gained popularity in scientific research focused on drug innovation against H. pylori because of their broad flexibility and low toxicity. The aim of this study was to describe the use of natural products against H. pylori in order to clarify important parameters for related fields. The study demonstrated the vast therapeutic possibilities for compounds originating from natural sources and revealed the need for innovations from future investigations to expand the therapeutic arsenal in the fight against H. pylori infection.
Keywords: Helicobacter pylori; Natural products; Antimicrobial activity